2018
DOI: 10.1093/jn/nxy008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fermentable Fibers Attenuate Chronic Kidney Disease in Mice by Protecting the Intestinal Barrier

Abstract: Supplemental feeding with fermentable DFs, such as GG and PHGG, might be effective for the prevention or management of CKD by restoring colonic barrier integrity and microflora composition, as shown in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…Multiple aspects of mucus and epithelial barrier integrity were enhanced (Monk et al, 2017). Similarly, feeding fermentable dietary fibre to mice increased faecal SCFA and protected the colonic barrier by increased expression of TJ proteins (ZO-1 and ZO-2, occluding, junctional adhesion molecule A (JAMA) and claudin-7) (Hung and Suzuki, 2018). When genetically obese mice (ob/ob) were fed a prebiotic-enriched diet, intestinal permeability was reduced and tight-junction integrity (expression of ZO-1 and occludin) was increased.…”
Section: Short Chain Fatty Acids Gut Permeability and Tight Junctionsmentioning
confidence: 99%
“…Multiple aspects of mucus and epithelial barrier integrity were enhanced (Monk et al, 2017). Similarly, feeding fermentable dietary fibre to mice increased faecal SCFA and protected the colonic barrier by increased expression of TJ proteins (ZO-1 and ZO-2, occluding, junctional adhesion molecule A (JAMA) and claudin-7) (Hung and Suzuki, 2018). When genetically obese mice (ob/ob) were fed a prebiotic-enriched diet, intestinal permeability was reduced and tight-junction integrity (expression of ZO-1 and occludin) was increased.…”
Section: Short Chain Fatty Acids Gut Permeability and Tight Junctionsmentioning
confidence: 99%
“…Fecal levels of acetate, propionate, and butyrate are increased following dietary fiber fermentation by gut bacteria [36], and accordingly, fiber-based interventions would be expected to positively affect the kidney-gut-muscle axis in animal models of ESRD. In support of this, fecal SCFAs are increased, renal and intestinal barrier function are improved, and circulating levels of urea and PCS are decreased in response to dietary fiber supplementation [23,37]. Although Van Hung et al and Yang et al [23,37] did not evaluate the effect of dietary fiber on intestinal Enterobacteriaceae abundance or on skeletal muscle, alternatively, intramuscular lipid content was reduced in conjunction with decreased circulating levels of PCS in response to dietary fiber supplementation with arabino-xylo-oligosaccharides (AXOS) [19].…”
Section: Gut-derived Uremic Metabolites Negatively Affect Skeletal Mumentioning
confidence: 90%
“…In support of this, fecal SCFAs are increased, renal and intestinal barrier function are improved, and circulating levels of urea and PCS are decreased in response to dietary fiber supplementation [23,37]. Although Van Hung et al and Yang et al [23,37] did not evaluate the effect of dietary fiber on intestinal Enterobacteriaceae abundance or on skeletal muscle, alternatively, intramuscular lipid content was reduced in conjunction with decreased circulating levels of PCS in response to dietary fiber supplementation with arabino-xylo-oligosaccharides (AXOS) [19]. SCFAs were not quantified in Koppe et al [19], but fecal levels of butyrate, and the sum of acetate, propionate, and butyrate are increased in response to AXOS feeding [38,39].…”
Section: Gut-derived Uremic Metabolites Negatively Affect Skeletal Mumentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, as CKD progresses, the accumulation of uremic toxins in CKD patients causes renal injury and fibrosis [ 19 ]. Recently, it was reported that CKD profoundly changes the intestinal microbial flora [ 20 ], leading to a suggestion that intervention for the gut microbiota derangements with probiotics and/or dietary fibers may be useful for decreasing the uremic toxin production and improve renal function [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%